2008
DOI: 10.1007/s12149-008-0163-y
|View full text |Cite
|
Sign up to set email alerts
|

QRS complex duration and dipyridamole gated SPECT findings in the left bundle branch block

Abstract: Our results demonstrated that the presence and severity of artifactual perfusion abnormalities owing to LBBB were significantly related to minimum QRS duration. The magnitude of perfusion abnormalities especially on the end-systolic phase seems to adversely affect systolic function of the left ventricle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“… 25 Such a relationship could not be found in our study. In contrast, a study by Inanir et al 26 found a correlation between minimum QRS duration and severity of MPS perfusion abnormalities in patients with LBBB. They also chose to evaluate the maximum and mean QRS durations and they found no correlation between mean QRS duration, consistent with our study, or maximum QRS duration and uptake defects on MPS images.…”
Section: Discussionmentioning
confidence: 71%
“… 25 Such a relationship could not be found in our study. In contrast, a study by Inanir et al 26 found a correlation between minimum QRS duration and severity of MPS perfusion abnormalities in patients with LBBB. They also chose to evaluate the maximum and mean QRS durations and they found no correlation between mean QRS duration, consistent with our study, or maximum QRS duration and uptake defects on MPS images.…”
Section: Discussionmentioning
confidence: 71%